Tariff elimination versus tax avoidance: Free trade agreements and transfer pricing - Hiroshi Mukunoki; Hirofumi Okoshi (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2020)
This study explores the new roles of rules of origin (ROO) when multinational enterprises (MNEs) manipulate their transfer prices to avoid a high corporate tax. ROO of a free trade agreement (FTA) require exporters to identify the origin of exports to be eligible for a preferential tariff rate. The results suggest that a value-added criterion of ROO restricts MNEs' abusive transfer pricing. Interestingly, an FTA with ROO can induce MNEs to shift profits from a low-tax country to a high-tax country. Because ROO augment tax revenues inside FTA countries, they can transform a welfare-reducing FTA into a welfare-improving FTA.
urn:nbn:de:bvb:19-epub-71608-6
Keywords: F13; F15; F23; H26; 330; Rules of origin; Free trade agreement; Transfer pricing